2017
DOI: 10.1055/s-0037-1598064
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Measurement of Absolute and Relative Judgments of Loudness: Clinical Relevance for Prescriptive Fitting of Aided Target Gains for soft, Comfortable, and Loud, But Ok Sound Levels

Abstract: This study was undertaken with the purpose of streamlining clinical measures of loudness growth to facilitate and enhance prescriptive fitting of nonlinear hearing aids. Repeated measures of loudness at 500 and 3,000 Hz were obtained bilaterally at monthly intervals over a 6-month period from three groups of young adult listeners. All volunteers had normal audiometric hearing sensitivity and middle ear function, and all denied problems related to sound tolerance. Group 1 performed judgments of and for presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Figure 9 ), taking the effect of compression into account still leaves output level differences in individual binaural loudness summation between 14 and 29 dB. These values are in accordance with the large interindividual differences in LDLs found by Formby et al. (2017) for monaural warble tones.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Figure 9 ), taking the effect of compression into account still leaves output level differences in individual binaural loudness summation between 14 and 29 dB. These values are in accordance with the large interindividual differences in LDLs found by Formby et al. (2017) for monaural warble tones.…”
Section: Discussionsupporting
confidence: 83%
“…Loudness complaints remain a major reason for revisiting the hearing aid dispenser (Jenstad, Van Tasell, & Ewert, 2003), and aversiveness of loud sounds is one of the main reasons to be dissatisfied with a hearing aid fitting (Hickson, Clutterbuck, & Khan, 2010). Discomfort of loud sound and its importance for hearing aid fitting have been extensively investigated (e.g., Formby, Payne, Yang, Wu, & Parton, 2017;Hawley, Sherlock, & Formby, 2017;Mueller & Bentler, 2005). The relationship between measured loudness discomfort levels and ratings for satisfaction, however, is weak (Zaugg, Thielman, Griest, & Henry, 2016), and the loudness judgments within the same loudness category varied across listeners within a group by as much as 50 to 60 dB (Formby et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…And this range increased further for loudness levels above 35 CU. This is in agreement with the findings from Formby et al (2017) who found loudness judgments within the same loudness category to vary across listeners by as much as 50-60 dB. Van Beurden et al (2018) found comparable ranges between lowest and highest levels judged to have equal loudness for international female noise and uniformly exciting noise of 17 Bark Bandwidth, presented unilaterally and bilaterally after narrowband loudness compensation.…”
Section: Discussionsupporting
confidence: 90%
“…In studies on the benefit of hearing aids aversiveness of loud sounds remains an important reason for dissatisfaction with hearing aids (Kochkin 2000;Jenstad, Van Tasell, and Ewert 2003;Boymans et al 2008;Hickson, Clutterbuck, and Khan 2010;Franks and Beckmann 1985;EuroTrak Germany 2018). However, in most clinical settings individual frequency-specific loudness discomfort levels (LDLs) are not routinely measured (Mueller 2003), as loudness measurements are deemed time-consuming and tedious for patients to perform (Formby et al 2017). In many hearing aid fittings, only hearing thresholds are included and the uncomfortable loudness level is estimated, for instance NAL-NL1 and NAL-NL2 do not allow to enter patient-specific LDLs (Keidser et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation